Documenting Angiosperm Diversity and Assigning Economic and Conservation Value of Kaan Forests: Traditionally Managed Climax Sacred Landscapes in Sagar Taluk of Central Western Ghats, India - Gunaga, Shrikant; N, Rajeshwari; R., Vasudeva (Asian Journal of Biological and Life Sciences, 2012)
The present study attempts to explore the traditionally managed Kaan forests in Sagar taluk of Central Western Ghats, Karnataka floristically. These Kaan forests are climax forest patches distributed along with agricultural and normal deciduous forest landscapes in the Malnad region literally meaning hilly landscapes of the Central Western Ghats. The angiosperm plant species were enumerated in selected four Kaan forests by laying transects covering a total area of 2 ha. The study of angiosperm floristic composition comprises of 59 families, 129 genera and 159 species. Of the total species, 119 (75%) species were evergreen, 108 (68%) endemic, 21 (13%) threatened and 149 (94 %) species were economically highly valued species. The study found that 93 species were medicinal, 50 species were fodder/manure species, 43 fuel wood species and 38 and 25 species were having timber and edible importance respectively. In this study we also tried to assess total importance value for each species by assigning scores to 10 different uses. The information of economic use for each species was gathered by consulting knowledgeable individuals and also by referring related literature. Study also tried to assign the conservation value of the Kaan forests.